Global trends in computing and communication systems: 4th International Conference, ObCom 2011, Vellore, TN, India, December 9-11, 2011. Proceedings, Part I - Babu, M. Rajasekhara; Ariwa, Ezendu; Krishna, P. Venkata (Communications in Computer and Information Science, 2012)
This two-volume set, CCIS 0269-CCIS 0270, constitutes the refereed post-conference proceedings of the International Conference on Global Trends in Computing and Communication, ObCom 2011, held in Vellore, India, in December 2011. The 173 full papers presented together with a keynote paper and invited papers were carefully reviewed and selected from 842 submissions. The conference addresses all current issues associated with computing, communication and information. The proceedings consists of invited papers dealing with the review of performance models of computer and communication systems and contributed papers that feature topics such as networking, cloud computing, fuzzy logic, mobile communication, image processing, navigation systems, biometrics and Web services covering literally all the vital areas of the computing domains.